Anaerobic selective fermentation of swine lagoon wastewater to valorize carbon into organic acids - Fernando, Priyasha (Kansas State University, 2022)
Volatile fatty acids (VFAs) are short-chain organic acids naturally generated from complex organic compounds through intermediate fermentation reactions during anaerobic digestion. VFAs serve as building blocks for many valuable commercial chemical products. This study aims to develop a modified fermentation biotechnology platform from swine wastewater coupled with membrane filtration aided by microbial electrochemistry. Controlled swine wastewater fermentation experiments were conducted with two different inocula (wastewater sludge and cattle rumen fluid), with or without a microbial bioanode. The key variables were temperature, pH, solid retention time (SRT)/hydraulic retention time (HRT), and the anode potential. A series of experiments were performed at different SRT conditions. Performance was characterized by electric current production, VFA quantification through high-performance liquid chromatography (HPLC), and gas chromatography (GC). At the 20-day SRT operation, sludge and rumen fermenters showed different organic acid profiles predominated by propionate/acetate and butyrate/acetate, respectively. However, acetate was the primary organic acid at 15-day SRT operation, with washout occurring at 10-day SRT for swine wastewater fermentation with sludge inoculum. The rumen inoculum suffered a faster washout of the fermentative microbial communities starting at 15-day SRT due to either lower active biomass concentration or the sensitivity of fermentative rumen microbial communities to swine wastewater. During Trial 2, caproate was prevalent during all phases of sludge fermenter operation (20, 15 and 10-day SRT). The rumen inoculum showed lactate and caproate as the dominant VFAs in the 20-day and 15-day SRT, respectively, during Trial 2. The microbial biofilm anode with wastewater sludge and swine wastewater exhibited a different fermentation product profile than non-electrode fermenters, with caproate predominance at 20-day SRT in both Trial 1 and 2. The anode area was observed as a rate-limiting step for kinetics and extent of swine wastewater fermentation. The recovery of VFAs from swine wastewater based on microbial reactions is becoming a promising research and development portfolio in the future due to its likely favorable life cycle and techno-economic footprints.
Keywords: Sustainability; Selective fermentation; Wastewater; Volatile fatty acids